VOLUMINOUS BAKER’S CYST IN THE RIGHT KNEE - Morais Moreira, Miguel Maximiano; Sant’Anna Aragão, Iapunira Catarina; Sant’Anna Aragão, Felipe Matheus; Aragão, José Aderval (Brazilian Journal of Implantology and Health Sciences, 2025)
Context: Baker’s cyst, also known as popliteal cyst, is one of the most common cystic affections in the posterior region of the knee. Its formation occurs due to the accumulation of synovial fluid in the gastrocnemius-semimembranosus bursa, frequently associated with intra-articular pathologies that elevate pressure within the knee. Although often asymptomatic, it can manifest with pain, swelling, and limited movement. Objective: This article aims to report a case of a voluminous Baker’s cyst in the right knee, highlighting its clinical and diagnostic characteristics and the response to conservative treatment. Case Report: A 54-year-old female patient presented with complaints of intense pain and a palpable mass in the right popliteal fossa. Diagnostic investigation via ultrasound revealed a large Baker’s cyst, measuring 7.9 x 1.6 x 5.2 cm, with internal debris. A notable finding was the absence of detectable underlying intra-articular pathologies by ultrasonography, with no apparent osteoarthritis. Treatment was based on non-steroidal anti-inflammatory drugs and physical therapy, resulting in significant clinical improvement for the patient within just two weeks. Conclusion: Baker’s cyst can be symptomatic due to its size or a one-way valve mechanism, even in the absence of evident joint lesions, reinforcing the need for an in-depth understanding of these factors for effective clinical diagnosis and management.